Frequency of health care provider recommendations for HPV vaccination: a survey in three large cities in China - Mao, Yimeng; Zhao, Yuchen; Zhang, Lingyun; Li, Jie; Abdullah, Abu S; Zheng, Pinpin; Wang, Fan (Frontiers in Public Health, 2023)
Introduction Human papillomavirus (HPV) infection, an important pathogenic factor for cervical cancer, can be prevented by the HPV vaccine. Health care provider (HCP) recommendations contribute to improve HPV vaccination coverage. The aim of this study was to assess the frequency of HCP recommendations for HPV vaccination and associated factors. Methods From Nov 8 to Dec 6 in 2018, a cross-sectional study was conducted through online questionnaires among HCPs (n = 1,371) from hospitals in three large cities in China (Shanghai, Guangzhou, and Shenzhen). Data on demographic characteristics, the frequency of HPV vaccination recommendations, HPV knowledge and related attitudes were collected through the questionnaires. Results Among 1,371 participants, only 30.2% reported that they frequently recommended HPV vaccination. Multivariate analyses indicated that female sex, being employed in obstetrics or gynecology departments and community health service centers, and having higher self-reported and actual knowledge of HPV were factors associated with a higher recommendation frequency. Factors including a self-perceived non-obligation to provide recommendations and difficulties in discussing sexual topics were significantly correlated with less frequent recommendations. Employment in a community health service center (OR = 2.068, 95% CI: 1.070–3.999) was the strongest factor associated with the frequency of HCPs’ recommendations for HPV vaccination. Discussion The frequency of HCPs’ recommendations for HPV vaccination in China was much lower than that in many developed countries. To enhance the recommendation frequency, medical institutions should help HCPs gain more knowledge of HPV and master communication skills. At the same time, the government should take measures to enhance the accessibility of HPV vaccines. The media should help to alleviate people’s concerns and encourage them to face up sexual health.